The Diagnostic Dilemma of the Most Common Yet the Most Complicted Malignancy Involving the Retromolar Region: A Case Report - Tanha Khan; M. K. Sunil; Megha Srivastava; Arpan Manna; Chhavi Srivastava; Lakshay Vishnoi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The most common type of oral malignant neoplasm is reported to be Oral Squamous Cell Carcinoma (OSCC),accounting for more than 90% of all malignant lesions in the oral cavity. The commonest site of OSCC arethe tongue, oropharynx and the floor of the mouth. OSCC is more common in men as compared to womenas men are often more associated with habits such as smoking and tobacco chewing. It is important to haveproper knowledge of this disease so that early diagnosis can be done and mortality rate can be reduced.